The Diachrony of Ditransitives in Late Modern Swedish - Valdeson, Fredrik (Brill's Studies in Historical Linguistics, 2024)
This book presents the first major study of ditransitives in Swedish. Using a combination of well-established and innovative corpus-based methods, the book reveals considerable changes in the constructional behaviour of ditransitive verbs over the course of the last 200 years. The key finding is that the use of the so-called double object construction has decreased dramatically in terms of frequency, lexical richness and semantic range. This development is parallelled by a decisive increase in prepositional object constructions. The results are of high relevance to the ongoing debate within construction grammar on constructional productivity and on the nature of horizontal links.